2003
DOI: 10.1046/j.1365-2427.2003.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

The ciliate epibiont Epistylis pygmaeum: selection for zooplankton hosts, reproduction and effect on two rotifers

Abstract: SUMMARY 1. A clonal culture of the peritrich Epistylis pygmaeum was used for all observations and experiments. Motile cells preferentially attached to the eggs of three species of Brachionus but also attached to the body of adult B. angularis. Zooids on the transitory egg substratum developed only short stalks, while those on the body often developed long stalks and branched colonies. Selection for the eggs positions the ciliate near the cloaca, and thus high concentrations of fine particulate material excrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 19 publications
2
37
1
Order By: Relevance
“…This species was referred to as E. senta in previous publications (Schröder, 2001(Schröder, , 2003Gilbert & Schröder, 2003;Schröder & Gilbert, 2004;Schröder, 2005). …”
Section: Commentsmentioning
confidence: 99%
“…This species was referred to as E. senta in previous publications (Schröder, 2001(Schröder, , 2003Gilbert & Schröder, 2003;Schröder & Gilbert, 2004;Schröder, 2005). …”
Section: Commentsmentioning
confidence: 99%
“…Studies emphasizing epibiont host specificity have pointed out that some peritrichs are able to attach to only one or two host species, failing to colonize non-living substrates (Clamp, 1973;Henebry and Ridgeway, 1979;Gilbert and Schröder, 2003). By contrast, some authors demonstrated that other epibionts are opportunistic, being able to attach to living or non-living substrates (Mayén-Estrada and Aladro-Lubel, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The only other record of growth rates estimated in the laboratory for a peritrich epibiont is that of Gilbert and Schröder (2003), who observed colony development of Epistylis pygmaeum attached to Brachionus angularis. They reported an exponential increase in zooids and the colonies originated from a single attached zooid, but the actual growth rates were not calculated for the trophont stage.…”
Section: Discussionmentioning
confidence: 99%
“…They sampled colonies of Carchesium polypinum Linnaeus, 1758 and individuals of Vorticella microstoma Ehrenberg, 1830 attached to transparent plastic films and found growth rates of 1.37 and 1.01 per day for the two peritrichs respectively. Considering peritrichs as epibionts, only one study so far, performed by Gilbert and Schröder (2003) has dealt with growth rates of peritrichs attached to living substrates in the laboratory. The authors observed an exponential growth of colonies of Epistylis pygmaeum Ehrenberg, 1838, from a single zooid, attached to the rotifer Brachionus angularis (Gosse, 1851), but no actual growth or colonization rates were calculated for the trophont stage of this species.…”
Section: Introductionmentioning
confidence: 99%